Strategi Pemasaran Lele Sangkuriang Organik Surya Kencana Farm Kota Bogor - Rabilla, Raissa Rahmaditya; Satria, Arif; Yuliati, Lilik Noor (Institut Pertanian Bogor, 2018)
Catfish is one of the most widely cultivated freshwater fish. Bogor is a district and a city that has considerable potential for Catfish farming. This is because the consumption of Catfish is pretty much absorbed by the DKI Jakarta and Bogor city become penyedianya. In 2016 alone, the level of consumption of Catfish in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) is very high. The needs of Jabodetabek community will Catfish reaches 120 tons per day. As quoted from an article, from the amount of these needs, Bogor can only produce Catfish as much as 30 tons per day. This of course becomes an opportunity and a prospect for Catfish farming. This study aims to identify the condition of internal environment and external environment in Surya Kencana Farm. Formulate alternative marketing strategies for Surya Kencana Farm. Determining priority marketing strategy for Surya Kencana Farm. This study uses SWOT analysis to determine alternative choice of marketing strategy for Surya Kencana Farm. Then proceed with QSPM to determine the best strategy that Surya Kencana Farm can do. The results of the analysis with the SWOT and QSPM matrices, obtained alternative strategies that can be implemented, namely utilizing IT progress, such as websites and the internet to inform Lele Sangkuriang product quality, and informing about organic Sangkuriang Catfish produced by SKF is a priority strategy that can be done by SKF.